Intracellular readthrough of nonsense mutations by aminoglycosides in coagulation factor VII - Mirko Pinotti (2018)
Background: Nonsense mutations in coagulation factor (F) VII potentially cause a lethal hemorrhagic diathesis. Readthrough of nonsense mutations by aminoglycosides has been studied in a few human disease models with variable results. Objectives: We investigated the K316X and W364 FVII mutations, associated with intracranial hemorrhage, and their correction by aminoglycosides. The rare nonsense mutations in FVII represent favorite models to test this strategy, because even tiny increases in the amount of functional fulllength protein in patients could ameliorate hemorrhagic phenotypes. Results: A FVII-green fluorescent protein (GFP) chimaera provided us with a fluorescent model of FVII expression in living cells. Appreciable fluorescence in cells transfected with nonsense FVII-GFP mutants was detected upon geneticin treatment, thus demonstrating suppression of premature translation termination. To investigate the rescue of FVII function, nonsense variants of the native FVII without GFP (p316X-FVII and p364X-FVII) were transfected and found to secrete low amounts of FVII (∼1% of Wt-FVII activity), thus suggesting a spontaneous stop codon readthrough. Geneticin treatment of cells resulted in a significant and dose-dependent increase of secreted FVII molecules (p316X-FVII, 24 ± 12 ng mL)1, 3.6 ± 0.8% of Wt-FVII activity; p364X-FVII, 26 ± 10 ng mL)1, 3.7±0.6%) characterized by reduced specific activity, thus indicating the synthesis of dysfunctional proteins. Similar results were observed with gentamicin, a commonly used aminoglycoside of potential interest for patient treatment. Conclusions: Our approach extendable to other coagulation factors, represents an effective tool for a systematic study of the effects of aminoglycosides and neighboring sequences on nonsense codon readthrough. These results provide the rationale for a mutation-specific therapeutic approach in FVII deficiency. © 2006 International Society on Thrombosis and Haemostasis.